Company Profile Distro DEVGRU CLOTHING using Multimedia Method - Mustagfirin Mustagfirin (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Now it needs the information or announcement ease in information technology in search of desired information as well as reduce error flags caused by human error . The developers of the internet now have started to grow very rapidly. Because almost all people around the world use the internet , that serves as aspects of a communication , information and facilities for the promotion of providers. Distro business “DEVGRU CLOTHING”Is a company move in production and sale of a garment ( clothes , a jacket , pants , hat ) asesoris and other .But in the selling process still use manual way and promotion and have not had a system information that supports. The use of information technology in the form of information systems can be used to improve their performance in terms of promotion or sale .So that could include the broader market.   Keywords: Design, Website Company Profile, Interactive Multimedia